The Effect of Vertical Sleeve Gastrectomy on a Rat Model of Polycystic Ovarian Syndrome - Wilson-Pérez, Hilary E. (Endocrine Society, 2011)
Polycystic ovarian syndrome (PCOS) is the most common endocrine disorder of women of reproductive age. Although some of the primary symptoms of PCOS are reproductive abnormalities, including hyperandrogenism, menstrual dysfunction, and hirsutism, other metabolic disturbances are also common, including obesity and insulin resistance. Women with PCOS who have undergone weight-loss bariatric surgery have reported surprising postoperative benefits beyond weight loss, including resolution of menstrual dysfunction and improvement of hirsutism. Here, we use a chronic dihydrotestosterone (DHT) exposure model of PCOS in female rats and investigate the efficacy of a specific type of bariatric surgery, namely vertical sleeve gastrectomy (VSG), to resolve the reproductive and metabolic disturbances induced by DHT treatment. We find that VSG causes loss of body weight and body fat in DHT-treated rats but does not improve glucose tolerance or restore estrous cyclicity. Although human PCOS patients have shown decreased androgen levels after bariatric surgery, the chronic nature of DHT administration in this rat model both before and after VSG renders this effect impossible in this case. Therefore, the lack of improvement in glucose tolerance and estrous cyclicity may implicate a direct effect of androgen knockdown as a mechanism for the improvements seen in human PCOS patients after bariatric surgery. In addition, the dissociation of body weight loss without improved glucose tolerance suggests that glucose intolerance may be a body weight-independent phenomenon in women with PCOS.